Plant Proteomics Methods and Protocols - Jorrin-Novo, Jesus V.; Valledor, Luis; Castillejo, Mari Angeles; Rey, Maria-Dolores (Methods in Molecular Biology, 2020)
XV, 417 p. 81 illus., 65 illus. in color.